Services Quality or Sharia Compliance? Factors which mostly Influence Customer Selection of Islamic Banks – The Case of Tanzania - Mussa K. Ramadhani; Mahmut Bilen (Türkiye İslam İktisadı Dergisi)
In the realm of banking, Islamic banking concepts and practices may appear unfamiliar to certain customers, particularly those transitioning from conventional banking systems. The perception of customers is significantly influenced by the level of education and awareness imparted by the banks themselves. Moreover, it is widely believed that customer perception directly impacts their satisfaction levels. Within Tanzania, the Islamic banking sector has experienced modest growth in recent years. This study aims to delve into the perception held by customers regarding Islamic Banks’ adherence to Shariah principles in their operations. Also, it aims to understand the factors that attract customers to Islamic banks instead of conventional ones. This research focuses on the Islamic banking industry in Tanzania, covering both the mainland and the Island of Zanzibar. A total of 305 Islamic bank customers participated in this study by completing a close-ended questionnaire. Using a descriptive research design, this study examined four key factors: the banks’ compliance with Shariah principles, customers’ awareness of Islamic banking products and services, criteria used by customers when selecting a bank, and customer satisfaction with the quality of services offered. The findings showed that the majority of Islamic bank customers in Tanzania perceived these banks to be operating in accordance with Shariah law. This study also highlighted that Shariah compliance was the primary influencing factor in choosing an Islamic bank over a conventional followed by service quality. Therefore, Islamic banks in Tanzania should focus on providing more education about Islamic banking and ensuring that their products align with Islamic law.